(untitled) (Journal of Hama University, 2019)
The preparation of root canals is one of the most important phases in the course of the endodontic treatment. that is a process that aims to obtain a tapered form gradually from the orifice towards the anatomic apex. This allows sufficient irrigation and disinfection for the complex root canal system, with as much preservation as possible in the initial form of the channel. From here, the development of techniques used in the root canal preparation began to achieve this goal; many techniques began to emerge such as rotary systems, with different designs and way of work.The aim of this study is to compare the effectiveness of two motorized preparation systems in the preparation of double-curved root canal simulations: 1-Hyflex 2-Magic Thirty resin blocks were used, containing a double-curved canal for each, divided into two groups; each group consists of 15 canals (n=15). The comparison between the canals was done on 12 levels before and after the preparation until the file size of 25. Then the data was recorded and the statistical analysis was performed at 95% confidence level. In the study of the effect of the studied part on the values of resin removed according to the preparation system used, the amount of resin removed from the right side was more than that of the left side, which led to a deflection in the canal to the right side in all preparation systems. But the amount of resin removed from the right side was larger in the Magic system than the Hyflex system, which led to more deflection of the canals to the right side in the Magic system. As for apex zipping, The results of this study showed that the number of cases where there was no apex displacement was the largest in the Hyflex preparation systemThe Hyflex system maintained the centrality of the canal somewhat with a slight deflection to the right, while the canal deflection to the right was evident in the Magic group.The results of this study showed that the number of cases where there was no apex displacement was the largest in the Hyflex preparation system